2020
DOI: 10.3390/coatings10050504
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Conductive Mechanism of Amorphous IGO Resistive Random-Access Memory with Different Top Electrode Metal

Abstract: In this paper, resistive random-access memory (RRAM) with InGaO (IGO) as an active layer was fabricated by radio-frequency (RF) sputtering system and the resistive switching mechanism with the different top electrode (TE) of Pt, Ti, and Al were investigated. The Pt/IGO/Pt/Ti RRAM exhibits typical bipolar resistive switching features with an average set voltage of 1.73 V, average reset voltage of −0.60 V, average high resistance state (HRS) of 54,954.09 Ω, and the average low resistance state (LRS) of 64.97 Ω, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The experimental details are the same as those of our previous work with TE of Al. 28 Table 1 summarizes several basic parameters of the RRAM device with different IGO switching layers. A significant difference in the forming voltages between stacked IGO and the others can be observed.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The experimental details are the same as those of our previous work with TE of Al. 28 Table 1 summarizes several basic parameters of the RRAM device with different IGO switching layers. A significant difference in the forming voltages between stacked IGO and the others can be observed.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In previous work, we have discussed different mechanisms of the reset process with different TEs. 28 There are two main mechanisms that affect the filament, oxidation–reduction (redox) reaction, and Joule heat effect. The redox reaction is due to oxidation and reduction of oxygen vacancies in the switching layer to form or destroy the filament.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, several studies have indicated that different top electrodes (TEs) may interact with the switching layer and affect performance. 8,9 Considering the above concerns, different oxygen flows of single-layer Ga 2 O 3 with three different TEs (Al, Ti, and Pt) were fabricated and investigated in this study. To improve the endurance, ZnO was stacked on Ga 2 O 3 to create a native gradient of oxygen vacancy concentration.…”
mentioning
confidence: 99%